THE ROLE OF LONG-TERM MEMORY IN QUR'AN LEARNING: COGNITIVE NEUROSCIENCE PERSPECTIVES - Permadi, Adi; suyadi (As-Sulthan Journal of Education, 2025)
Memorizing the Qur’an (tahfidz) constitutes a fundamental practice within Islamic education that integrates spiritual discipline with complex cognitive mechanisms. This study investigates the role of long-term memory in tahfidz learning through a cognitive neuroscience framework. Employing a literature review approach, the analysis synthesizes scholarly sources in neuroscience, cognitive psychology, and Islamic pedagogy to elucidate how memory processes—encoding, consolidation, storage, and retrieval—operate in Qur’anic memorization. The reviewed evidence indicates that neural structures including the hippocampus, prefrontal cortex, medial temporal cortex, and amygdala play essential roles in organizing, stabilizing, and retrieving memorized verses. Empirical findings also support the effectiveness of strategies such as spaced repetition, mushaf-based visual mapping, semantic association, and mnemonic patterning in strengthening synaptic connectivity and retention. Furthermore, emotional regulation and spiritual engagement are shown to facilitate memory consolidation via activation of the limbic system, while restorative sleep, peer interaction, and collaborative learning in halaqah settings enhance long-term recall. Collectively, these insights demonstrate that tahfidz represents a holistic neurocognitive process that synergistically integrates devotional motivation, affective states, and memory system dynamics. The study underscores the pedagogical significance of developing neuroscience-informed tahfidz methodologies that align cognitive, emotional, and spiritual elements within instructional design. Future research opportunities include experimental neuroeducation models to quantitatively evaluate the efficacy of memory-enhancement protocols in broader Islamic learning contexts.